Stability of nanofluids: Molecular dynamic approach and experimental study. (1st March 2016) - Farzaneh, H.; Behzadmehr, A.; Yaghoubi, M.; Samimi, A.; Sarvari, S.M.H.
Highlights: Nanofluid stability is investigated and discussed. A molecular dynamic approach, considering different forces on the nanoparticles, is adopted. Stability diagrams are presented for different thermo-fluid conditions. An experimental investigation is carried out to confirm the theoretical approach. Abstract: Nanofluids as volumetric absorbent in solar energy conversion devices or as working fluid in different heat exchangers have been proposed by various researchers. However, dispersion stability of nanofluids is an important issue that must be well addressed before any industrial applications. Conditions such as severe temperature gradient, high temperature of heat transfer fluid, nanoparticle mean diameters and types of nanoparticles and base fluid are among the most effective parameters on the stability of nanofluid. A molecular dynamic approach, considering kinetic energy of nanoparticles and DLVO potential energy between nanoparticles, is adopted to study the nanofluid stability for different nanofluids at different working conditions. Different forces such as Brownian, thermophoresis, drag and DLVO are considered to introduce the stability diagrams. The latter presents the conditions for which a nanofluid can be stable. In addition an experimental investigation is carried out to find a stable nanofluid and to show the validity of the theoretical approach. There is a good agreement between the experimental and theoretical results that confirms the validity of our theoretical approach.